Analisis Ketersediaan Air Daerah Tangkapan Air Dait Sebagai Sumber Energi Terbarukan - Lambok M Sitinjak; Hardiansyah Hardiansyah; Nurhayati Nurhayati (Universitas Tanjungpura, 2022)
Limited coverage of the PLN electricity network to villages from urban and isolated, resulting in people not being able to enjoy electric energy and those who are economically able to use electric diesel engines as an energy source. Some people who are economically able to use electric diesel engines as a source of energy, but because fuel oil has become increasingly expensive and scarce these days, the operating costs of diesel engines are high, so the diesel engine is no longer operated. Utilizing the potential of renewable energy in the form of local water resources as a source of electrical energy is an alternative solution to solve energy problems. This concept is based on microhydro power plant technology. Micro hydro is usually used for power plants with the greatest power with capacity of 100 kW. Sekendal Village, Air Besar District, Landak Regency, has the potential of a waterfall that has not been utilized. This study aims to analyze water availability of Dait watershed as renewable energy. The availability of water was analyzed using the Mock method and calibrated with the results of measurements in the field. The results showed reliable discharge value of 90% obtained the value of Q = 0.165 m3/s, the height of the water fall (Head) H = 30 m and the power that can be generated is 40.19 Kw. Keywords: discharge, dependable discharge, microhydro power plant, head, renewable energy Abstrak Keterbatasan jangkauan jaringan listrik PLN ke desa-desa yang jauh dari perkotaan dan terisolir, mengakibatkan masyarakat tidak bisa menikmati energi listrik. Sebagian masyarakat yang mampu secara ekonomi menggunakan mesin diesel listrik sebagai sumber energi, namun karena bahan bakar minyak akhir-akhir ini semakin mahal dan langka mengakibatkan biaya operasional mesin diesel tinggi sehingga mesin diesel tersebut tidak dioperasikan lagi. Memanfaatkan potensi energi baru terbarukan berupa sumber daya air setempat sebagai sumber energi listrik merupakan alternatif solusi pemecahan masalah energi. Konsep ini berbasis pada teknologi pembangkit listrik tenaga mikrohidro. Mikrohidro biasanya dipakai untuk pembangkit listrik dengan kapasitas daya paling besar 100 kW. Desa Sekendal Kecamatan Air Besar Kabupaten Landak memiliki potensi air terjun yang belum dimanfaatkan. Penelitian ini bertujuan untuk menganalisis ketersediaan air di sub daerah aliran Sungai Dait sebagai sumber energi. Ketersediaan air dianalisis menggunakan metoda Mock dan dikalibrasi dengan hasil pengukuran debit air sungai. Hasil penelitian menunjukkan besarnya debit andalan 90% atau Q 90 adalah 0,165 m3/s, tinggi jatuh air H=30 m dan daya yang mampu dibangkitkan adalah sebesar 40,19 Kw.